2004
DOI: 10.1090/s0025-5718-04-01636-9
|View full text |Cite
|
Sign up to set email alerts
|

Improved methods and starting values to solve the matrix equations $X\pm A^*X^{-1}A=I$ iteratively

Abstract: Abstract. The two matrix iterations X k+1 = I ∓ A * X −1 k A are known to converge linearly to a positive definite solution of the matrix equations X ± A * X −1 A = I, respectively, for known choices of X 0 and under certain restrictions on A. The convergence for previously suggested starting matrices X 0 is generally very slow. This paper explores different initial choices of X 0 in both iterations that depend on the extreme singular values of A and lead to much more rapid convergence. Further, the paper offe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 14 publications
0
29
0
Order By: Relevance
“…In the last few years, there has been a constantly increasing interest in developing the theory and numerical approaches for HPD (Hermitian positive definite) solutions to different classes of nonlinear matrix equations (see [8][9][10][11][12][13][14][15][16][17][18][19][20][21]). In this study, we consider the following problem: Find (X 1 , X 2 , ..., X m ) (P(n)) m solution to the following system of nonlinear matrix equations:…”
Section: Resultsmentioning
confidence: 99%
“…In the last few years, there has been a constantly increasing interest in developing the theory and numerical approaches for HPD (Hermitian positive definite) solutions to different classes of nonlinear matrix equations (see [8][9][10][11][12][13][14][15][16][17][18][19][20][21]). In this study, we consider the following problem: Find (X 1 , X 2 , ..., X m ) (P(n)) m solution to the following system of nonlinear matrix equations:…”
Section: Resultsmentioning
confidence: 99%
“…[23,28,32,[45][46][47]. This is because this equation, as already mentioned, is a special case of the Riccati equation, which plays a key role in various problems of synthesis of control systems [16, 39, 41, 43, etc.].…”
Section: Special Casementioning
confidence: 99%
“…(1.4). As a rule, such algorithms are iterative, which leads to the additional task of choosing the initial approximation [28]. In what follows, we will show that algorithms based on LMI-solution procedures can be used in some cases to find the maximum and minimum solutions of Eq.…”
Section: Equation (14) [42] Equation (14) Plays An Important Role mentioning
confidence: 99%
See 1 more Smart Citation
“…During the last few years, many researchers worked to develop the theory and numerical approaches for positive definite solutions to the nonlinear matrix equations of the form (1) [6][7][8][9]. Recently, Duan et al [10] showed that the equation − ∑ =1 * = (0 < | | < 1) always has a unique positive definite solution by using the fixed point theorem of mixed monotone operators.…”
Section: Introductionmentioning
confidence: 99%